(untitled) (Bangladesh Journal of Anatomy, 2015)
Context: Skinfold thickness is one of the important parameter to assess nutritional status which is widely used in children. It is the common technique for estimating fat mass in children. We can also use measurement of skinfold thickness in children for clinical, research and epidemiological purposes. The present study was planned to determine difference in skinfold thickness between boys and girls of four government primary school in Dhaka city. Materials & Methods: A cross-sectional analytical type of study was conducted in the department of anatomy, Dhaka Medical College, Dhaka, from January 2012 to December 2012. The present study was performed on 400 government primary school children. Out of 400 children, 200 were boys and 200 were girls. The study population was divided into three groups A, B, C according to age and sex of the subject. Group A include age 9+ years, group B include age 10+ years and group C include age 11+ years old children. Each group was again subdivided into A1, B1 and C1 for boys and A2, B2 and C2 for girls. The subjects of this age group were the students of class III to class V. With the help of skinfold caliper measurements were recorded. Results: Triceps, subscapular, suprailiac and medial calf skinfold of group A2, B2 and C2 were significantly greater (P<0.001) than group A1, B1 and C1. Bangladesh Journal of Anatomy July 2015, Vol. 13, No. 2, pp. 41-45